Effects of zolpidem and zaleplon on cognitive performance after emergent morning awakenings at Tmax: a randomized placebo-controlled trial. Issue 3 (18th December 2018) - Dinges, David F; Basner, Mathias; Ecker, Adrian J; Baskin, Pamela; Johnston, Smith L
Abstract: Study Objectives: Prescription sleep aids are frequently used in the general population and even more frequently in spaceflight. To evaluate the risk to operational safety, a ground-based, double-blind, placebo-controlled study on the emergent awakening effects of zolpidem and zaleplon was conducted. Methods: N = 34 participants (age M = 42.1 ± 9.7; 25 males; 9 Astronauts, 7 Astronaut candidates, and 18 Flight Controllers) were investigated for three nights separated by M = 10 days. They were randomized to ingestion of one of the following at lights out: placebo, 10 mg zaleplon, and either 5 mg ( N = 20) or 10 mg ( N = 14) zolpidem. They were awakened abruptly by alarm at the expected P K, max (1 hr after lights out for zaleplon; 1.5 hr for placebo/zolpidem). Participants were required to turn off the alarm and perform a cognitive test battery twice, separated by a 20–30 min reading break. They then returned to sleep and were awakened to perform the same cognitive tasks at an average of 6.7 hr after drug ingestion. Results: Relative to placebo, the effects of 10 mg zaleplon and 5 mg zolpidem on cognitive performance were minor. In contrast, 10 mg zolpidem adversely affected cognitive throughput ( p < 0.001), psychomotor vigilance ( p < 0.001), working memory ( p < 0.01), delayed word recall ( p < 0.05), and subjective sleepiness ( p < 0.01) at the first emergent awakening. At terminal awakening, neither cognitive performance nor subjective sleepiness was impaired after ingestion of zaleplon or zolpidem (5 mg and 10 mg) compared with placebo. Conclusions: Presleep ingestion of sleep medications, especially 10 mg zolpidem, poses a risk for performance errors after emergent awakenings near the expected P K, max . Registration: Optimize Astronaut Sleep Medication Efficacy and Individual Effects (clinicaltrials.gov ID NCT03526575).